2020
DOI: 10.1002/smll.202005461
|View full text |Cite
|
Sign up to set email alerts
|

Actuating Supramolecular Shape Memorized Hydrogel Toward Programmable Shape Deformation

Abstract: Inspired by nature, diverse biomimetic hydrogel actuators are fabricated and become one of the most essential components of bionics research. Usually, the anisotropic structure of a hydrogel actuator is generated at the early fabrication process, only a specific shape transformation behavior can be produced under external stimuli, and thus has limited the development of hydrogel actuators toward the biomimetic shape deformation behavior. Herein, a novel bilayer hydrogel having a thermoresponsive actuating laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 42 publications
(50 reference statements)
0
44
0
Order By: Relevance
“…As shown in Figure 4a, the LCST of the conductive hydrogel was about 34 °C (PNIPAM has an LCST at around 32 °C in aqueous solutions. [34][35][36] ). It is concluded that LCST can be precisely justed by the content of the copolymer and the molar ratio of monomers.…”
Section: The Lcst Of the Hydrogelsmentioning
confidence: 99%
“…As shown in Figure 4a, the LCST of the conductive hydrogel was about 34 °C (PNIPAM has an LCST at around 32 °C in aqueous solutions. [34][35][36] ). It is concluded that LCST can be precisely justed by the content of the copolymer and the molar ratio of monomers.…”
Section: The Lcst Of the Hydrogelsmentioning
confidence: 99%
“…10a ). 88 Unlike in the case of traditional hydrogel actuators, in this system, temporary anisotropic structures could be formed and programmed using shape memory, and various morphing transformations could be induced by the actuating process. For instance, the wings of a butterfly-shaped bilayer hydrogel could first be fixed into a curved shape by metal ion–Alg interactions, and the wings could then deform from the curved shape into a soaring shape in response to a heat stimulus.…”
Section: Combined Shape Memory and Actuating Behaviormentioning
confidence: 99%
“…Electrical current is conducted by the migration of ions that results from adding inorganic salt, or ionic liquid and the conductivity could be simply tuned by the quantity of ions. Ionic conductive gels are usually endowed with stretchability, [12,42,53] compliance, [54,55] adhesive, [39,55] self-healing ability, [39,54,55] shape memory, [56] and transparent properties [24,39] by changing the precursor content and designing the polymer structure. They are promising materials for bionic skin, [26,[57][58][59][60][61] which are flexible ionic conductive polymer sensors that mimic the sensing functions of mammalian skin.…”
Section: Ionic Conductive Gelsmentioning
confidence: 99%